Oedipus The Ancient Legend and Its Later Analogues - Edmunds, Lowell (Johns Hopkins University Press, 2020)
Drawing on more than seventy works that dispersed the Oedipus legend from Greece to Asia, Africa, and the Americas, Edmunds provides a foundation for discussion of the lasting appeal of this legend, for claims of its universality, and for its uses as a vehicle for personal and cultural expression.The power of the Oedipus legend is apparent not only in its interpretations but even more so in its variations. As Edmunds writes, "Translations, adaptations, and performances still come forth in a never-ending stream. Again and again, playwrights have tried their hand at new shapings of the Sophoclean Oedipuses and often a country's Oedipus forms a whole chapter in the history of its literature." Drawing on more than seventy works that dispersed the Oedipus legend from Greece to Asia, Africa, and the Americas, Edmunds provides a foundation for discussion of the lasting appeal of this legend, for claims of its universality, and for its uses as a vehicle for personal and cultural expression.